Discriminazione e propaganda religiosa nel diritto calcistico (Stato, Chiese e pluralismo confessionale, 2015)
Il contributo è in corso di pubblicazione nel volume collettaneo, a cura di G. Mazzei, C. Espartero, Problematiche giuridiche e ruolo sociale dello sport – Problématica jurídica y papel social del deporte, ESI, Napoli, ed è stato già sottoposto a valutazioneSOMMARIO: 1. Cenni introduttivi a proposito degli ordinamenti sportivi – 2. La rilevanza del fattore religioso nel diritto sportivo – 3. La FIFA tra divieto di discriminazione e assenza di ulteriori norme specifiche di rilevanza religiosa – 4. La neutralità UEFA. La previsione congiunta dei divieti di discriminazione e propaganda anche religiosa – 5. La FIGC e le statuizioni nella materia de qua. La punizione della blasfemia – 6. Conclusioni interlocutorie. La regola 4 delle Laws of the Game tra divieto di propaganda e permesso di indosso di copricapi religiosi Discrimination and religious propaganda in football law   Abstract: After a brief review over sport legal system, the paper deals with the relationship between religion and sport, in a juridical perspective. First in general and then with regards of football at international, supranational and national level (FIFA; UEFA and FIGC), focusing on the ban of religious discrimination and the most recently interdiction of religious propaganda.Before concluding with some regards on the almost changed rules 4 of the “Laws of the Game” – that concurrently on the one hand allows head covers (hijab and turban) and on the other prohibits to reveal undergarments that show also religious slogans, statements or images, or advertising other than the manufacturer logo – the essay focuses on the peculiarity FIGC prescription to punish the use of blasphemy since 2010.